Quantum Interference and Coherence Theory and Experiments - Ficek, Zbigniew; Swain, Stuart; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2005)
For the first time, this book assembles in a single volume accounts of many phenomena involving quantum interference in optical fields and atomic systems. It provides detailed theoretical treatments and experimental analyses of such phenomena as quantum erasure, quantum lithography, multi-atom entanglement, quantum beats, control of decoherence, phase control of quantum interference, coherent population trapping, electromagnetically induced transparency and absorption, lasing without inversion, subluminal and superluminal light propagation, storage of photons, quantum interference in phase space, interference and diffraction of cold atoms, and interference between Bose-Einstein condensates. This book fills a gap in the literature and will be useful to both experimentalists and theoreticians.
Classical and Quantum Interference and Coherence -- Quantum Interference in Atomic Systems: Mathematical Formalism -- Superposition States and Modification of Spontaneous Emission Rates -- Quantum Interference as a Control of Decoherence -- Coherence Effects in Multi-Level Systems -- Field Induced Quantum Interference -- Slow and Fast Light and Storage of Photons -- Quantum Interference in Phase Space -- Quantum Interference in Atom Optics.
Keywords: Quantum optics; Atoms; Physics; Quantum Optics; Atomic, Molecular, Optical and Plasma Physics